Respuesta :
[tex](3y^4-5x^2y^2-6x^4)\,\mathrm dx-4xy^3\,\mathrm dy=0\iff\dfrac{\mathrm dy}{\mathrm dx}=\dfrac{3y^4-5x^2y^2-6x^4}{4xy^3}[/tex]
Multiplying both the numerator and denominator by [tex]\dfrac1{x^4}[/tex], we get
[tex]\dfrac{\mathrm dy}{\mathrm dx}=\dfrac{4\left(\frac yx\right)^4-5\left(\frac yx\right)^2-6}{4\left(\frac yx\right)^3}[/tex]
Since the derivative can be expressed as a function of [tex]\dfrac yx[/tex], the ODE is homogeneous. This means substituting [tex]y=xv[/tex] will be an effective approach. Indeed, we have [tex]\dfrac{\mathrm dy}{\mathrm dx}=x\dfrac{\mathrm dv}{\mathrm dx}+v[/tex], and the ODE can be rewritten as the separable equation
[tex]x\dfrac{\mathrm dv}{\mathrm dx}+v=\dfrac{3v^4-5v^2-6}{4v^3}[/tex]
[tex]x\dfrac{\mathrm dv}{\mathrm dx}=-\dfrac{v^4+5v^2+6}{4v^3}[/tex]
[tex]\dfrac{4v^3}{v^4+5v^2+6}\,\mathrm dv=-\dfrac{\mathrm dx}x[/tex]
[tex]\displaystyle\int\dfrac{4v^3}{v^4+5v^2+6}\,\mathrm dv=-\int\dfrac{\mathrm dx}x[/tex]
[tex]\displaystyle\int\left(\frac{12v}{v^2+3}-\dfrac{8v}{v^2+2}\right)\,\mathrm dv=-\ln|x|+C[/tex]
[tex]6\ln(v^2+3)-4\ln(v^2+2)=-\ln|x|+C[/tex]
[tex]\ln\dfrac{(v^2+3)^6}{(v^2+2)^4}=-\ln x+C[/tex]
[tex]\dfrac{(v^2+3)^6}{(v^2+2)^4}=\dfrac Cx[/tex]
[tex]\dfrac{\left(\frac{y^2}{x^2}+3\right)^6}{\left(\frac{y^2}{x^2}+2\right)^4}=\dfrac Cx[/tex]
[tex]\dfrac{(y^2+3x^2)^6}{x^4(y^2+2x^2)^4}=\dfrac Cx[/tex]
[tex]\dfrac{(y^2+3x^2)^6}{(y^2+2x^2)^4}=Cx^3[/tex]
You're welcome to unpack this further, but I would stop here.
Multiplying both the numerator and denominator by [tex]\dfrac1{x^4}[/tex], we get
[tex]\dfrac{\mathrm dy}{\mathrm dx}=\dfrac{4\left(\frac yx\right)^4-5\left(\frac yx\right)^2-6}{4\left(\frac yx\right)^3}[/tex]
Since the derivative can be expressed as a function of [tex]\dfrac yx[/tex], the ODE is homogeneous. This means substituting [tex]y=xv[/tex] will be an effective approach. Indeed, we have [tex]\dfrac{\mathrm dy}{\mathrm dx}=x\dfrac{\mathrm dv}{\mathrm dx}+v[/tex], and the ODE can be rewritten as the separable equation
[tex]x\dfrac{\mathrm dv}{\mathrm dx}+v=\dfrac{3v^4-5v^2-6}{4v^3}[/tex]
[tex]x\dfrac{\mathrm dv}{\mathrm dx}=-\dfrac{v^4+5v^2+6}{4v^3}[/tex]
[tex]\dfrac{4v^3}{v^4+5v^2+6}\,\mathrm dv=-\dfrac{\mathrm dx}x[/tex]
[tex]\displaystyle\int\dfrac{4v^3}{v^4+5v^2+6}\,\mathrm dv=-\int\dfrac{\mathrm dx}x[/tex]
[tex]\displaystyle\int\left(\frac{12v}{v^2+3}-\dfrac{8v}{v^2+2}\right)\,\mathrm dv=-\ln|x|+C[/tex]
[tex]6\ln(v^2+3)-4\ln(v^2+2)=-\ln|x|+C[/tex]
[tex]\ln\dfrac{(v^2+3)^6}{(v^2+2)^4}=-\ln x+C[/tex]
[tex]\dfrac{(v^2+3)^6}{(v^2+2)^4}=\dfrac Cx[/tex]
[tex]\dfrac{\left(\frac{y^2}{x^2}+3\right)^6}{\left(\frac{y^2}{x^2}+2\right)^4}=\dfrac Cx[/tex]
[tex]\dfrac{(y^2+3x^2)^6}{x^4(y^2+2x^2)^4}=\dfrac Cx[/tex]
[tex]\dfrac{(y^2+3x^2)^6}{(y^2+2x^2)^4}=Cx^3[/tex]
You're welcome to unpack this further, but I would stop here.